PROFEMINIS DAN KONTRAFEMINIS TOKOH HANAH DALAM CERPEN TELAPAK KAKI YANG MENYIMPAN SURGA KARYA NI KOMANG ARIANI - Siti Elly Irmawati; Evi Chamalah; Turahmat Turahmat (Jurnal Pendidikan Bahasa Indonesia, 2017)
The background of short story is about intricacies of Hanah’s household life, which shows the character of Hanah’s obidience that always be in theauthorization of man, that is her husband. This study in general aimed to obtainthe description about prosfeminism and consfeminism of Hanah's figure in theshort story Telapak Kaki yang Menyimpan Surgawhich was written by Ni Komang Ariani in the Jawa Pos newspaper whichis published on 18 September 2016. The method used in this study was descriptive qualitative methods. Furthemore the approach of feminism was done to knowing about prosfeminism and consfeminism of Hanah as a wife or women in general. The results of research showed that Hanah belonged consfeminism because she was more obeyed anything her husband's told then doing activity outside the house. But,actually Hanah wished to go to school and do activities outside the house because her husband demanded to commit polygamy.